2015
DOI: 10.1080/21645515.2015.1011999
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine attitudes and practices among obstetric providers in New York State following the recommendation for pertussis vaccination during pregnancy

Abstract: To determine factors associated with obstetric provider recommendation of pertussis vaccine (Tdap) to their pregnant patients following the Advisory Committee on Immunization Practices (ACIP) recommendation that Tdap be given in the third trimester of each pregnancy. Obstetric providers across New York State anonymously completed a standard set of questions to assess vaccine recommendation knowledge and practice. Statistical analysis: Descriptive statistical methods were used to define provider characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 17 publications
(20 reference statements)
4
38
1
Order By: Relevance
“…Moreover, 11% and 13% of them expressed concern about vaccine safety and efficacy, respectively, despite the growing body of literature against these beliefs 61. Concerns raised included vaccine price, the need to vaccinate in each pregnancy, vaccine safety and low incidence of pertussis in the area.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 11% and 13% of them expressed concern about vaccine safety and efficacy, respectively, despite the growing body of literature against these beliefs 61. Concerns raised included vaccine price, the need to vaccinate in each pregnancy, vaccine safety and low incidence of pertussis in the area.…”
Section: Resultsmentioning
confidence: 99%
“…Some patients and healthcare providers are hesitant to or do not vaccinate during pregnancy because of perceived (vaccine) safety [23][24][25]. Other barriers to vaccination during pregnancy from the patient and healthcare perspective include negative media, missed vaccination opportunity (immunization not offered or requested), lack of vaccine stock, inadequate reimbursement, and limited patient interest [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one study showed that providers play an important role in a pregnant woman’s decision to receive influenza vaccination; pregnant women who receive a recommendation and an offer of influenza vaccine are more likely to be vaccinated (70.5%) than women who received a recommendation but no offer (32.0%) or who received no recommendation and no offer (9.7%) [27]. A recent study from providers in New York state found that only 80% of obstetric providers recommended Tdap to all eligible patients, and 67% provided the vaccine in their office [28]. …”
Section: Discussionmentioning
confidence: 99%